Trait emotional intelligence and academic performance : controlling for the effects of IQ, personality, and self-concept - Ferrando, Mercedes (2011)
This article analyses the relationship between trait emotional intelligence and academic performance, controlling for the effects of IQ, personality, and self-concept dimensions. A sample of 290 preadolescents (11-12 years old) took part in the study. The instruments used were (a) Trait Emotional Intelligence Questionnaire–Adolescents Short Form (TEIQue-ASF); (b) Children’s Personality Questionnaire (CPQ; Form A, Part A); (c) IQ test TIDI-2; (d) Adaptation Questionnaire (CAI-1); and (e) academic performance. A positive and significant correlation coefficient between trait EI measured by the TEIQue-ASF and general academic performance was found. The TEIQue-ASF showed incremental validity to predict general academic performance, after controlling for intelligence, personality, and self-concept characteristics.